Malaria, urogenital schistosomiasis and co-infection and nutritional status of school children in Ondo state - Esther Mofiyinfoluwa Ola; Temitope Helen Balogun; Rasheed Olayinka Isijola; Oluwaremilekun Grace Ajakaye (PLoS ONE, 2025)
Parasitic infections are a major cause of morbidity and mortality in Nigeria, with malaria and schistosomiasis having the highest burden. This study investigated the prevalence of malaria, urogenital schistosomiasis, and co-infections and their impact on the nutritional status of schoolchildren in two communities in Ondo State. A total of 185 participants from Ipogun and Oke Igbo were screened for malaria and schistosomiasis infection using the ParaHit malaria rapid diagnostic test kit and urine microscopy. Anthropometric measurements were used to assess the nutritional status of the participants. In this study, a higher prevalence of malaria was recorded in Oke Igbo, with 36 individuals (57.1%), compared to 60 individuals (49.2%) in Ipogun. Urogenital schistosomiasis was also more prevalent in Oke Igbo, affecting 18 individuals (28.6%), while only 5 individuals (4.1%) were affected in Ipogun. Co-infection with both diseases was more common in Oke Igbo, with 13 cases (20.6%), compared to 4 cases (3.3%) in Ipogun. However, malnutrition rates were similar between the two communities, with 60 cases (77.9%) in Ipogun and 28 cases (75.5%) in Oke Igbo. Notably, participants with either malaria or urogenital schistosomiasis, as well as those co-infected, exhibited a higher frequency of chronic malnutrition. The likelihood of co-infection was significantly associated with gender and locality, with individuals in Oke Igbo being 0.78 times less likely to be co-infected (P = 0.00; CI = 0.09–0.49), while males were 2.19 times more likely to have co-infections (P = 0.02; CI = 1.13–4.28). This study emphasised the significant health burden posed by malaria and urogenital schistosomiasis co-infections among schoolchildren in Ondo State, highlighting the need for comprehensive health and nutritional interventions to address the challenges associated with these parasitic diseases.